Comparing the Pathway to Success in European Countries Competing in the Swimming World Championships - Yustres, Inmaculada; Santos del Cerro, Jesús; González-Mohíno, Fernando; Peyrebrune, Michael; González-Ravé, José María (Frontiers in Psychology, 2019)
Purpose: This study aimed to compare the performance progression model of the European countries that participated in the World Championships (WCs) from 2006 to 2017. Data from all championships were compared between the top 5 (1-5) and the next 5 (6-10) countries on the medal table. The study also identifies the ages of peak performance in senior swimmers, the annual ratio of progression and the effect of junior performance on senior success by these groups of countries. We hypothesized that: (a) countries with swimmers achieving better performances at the Junior WCs would also be higher in the medal ranking at the Senior WCs; (b) a higher annual performance progression in their swimmers increases the chances of countries being ranked in the top 5 at the Senior World Championships. Methods: Participant’s data from all Junior and Senior WCs between 2006 and 2017 were obtained from FINA. The final, filtered database included 629 swimmers after removing those participating only in the Junior WCs and selecting swimmers from the top 10 countries. One-way ANOVA, F test and decision tree methods were used to examine differences between the top (1-5) and the next best (6-10) countries on the medal table for first participation age, annual progress and best-time in junior and senior championships. Results: There was no difference (p = 0.492 and p=0.97) between 1-5 and 6-10 ranked countries for best senior time and annual progression respectively. Countries ranked in the top 5 at the Senior WCs had swimmers with faster times at the Junior WCs (p > 0.001). Decision tree analysis found that best-time at the Junior WC had the greatest explanatory capacity (94%). Conclusion: European countries with swimmers who perform best at the Junior WCs are also likely to be in the top 5 countries that win medals at the Senior WCs.